Characterization of Series Resistances and Mobility Attenuation Phenomena in Short Channel MOS Transistors - A. El Abbassi; Y. Amhouche; E. Bendada; R. Rmaily; K. Raïs (Active and Passive Electronic Components)
As the scaling proceeds, the transverse electric field increase, and a mobility attenuation phenomenon becomes of primordial interest. Indeed, the high transverse electric field is generally ascribed [1] to surface roughness scattering in the channel and consequently reduce effective mobility of carriers. In short channel MOSFET, the Source-Drain resistance Rsd influence strongly the effective mobility.